2018
DOI: 10.1103/physrevlett.121.091101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cosmic Rays on the Evolution and Momentum Deposition of Supernova Remnants

Abstract: Using a semianalytical approach based on the thin-shell approximation, we calculate the long-term evolution of supernova remnants (SNRs) while also accounting for the cosmic rays (CRs) accelerated at their blast waves. Our solution reproduces the results of state-of-the-art fluid simulations across the adiabatic and radiative stages for the gas-only case, and it predicts that typical CR acceleration efficiencies (≈10%) can boost SNR momentum deposition by a factor of 2-3. This enhancement can become as large a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 44 publications
1
48
4
Order By: Relevance
“…To further address the importance of the late times in SNR evolution for shaping the electron spectrum, we considered a rather extreme situation in which particle acceleration is efficient until 80 kyr. Indeed, it has been shown that the duration of the ST phase can be substantially extended, for instance because of the CR pressure on the SNR shock (Diesing & Caprioli 2018). In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further address the importance of the late times in SNR evolution for shaping the electron spectrum, we considered a rather extreme situation in which particle acceleration is efficient until 80 kyr. Indeed, it has been shown that the duration of the ST phase can be substantially extended, for instance because of the CR pressure on the SNR shock (Diesing & Caprioli 2018). In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we assume E SN = 10 51 erg, M ej = 1 M , and n 0 = 1 cm −3 as reference values for type Ia SNe. It is worth recalling that in the presence of efficient CR acceleration at the SNR shock, as discussed by Diesing & Caprioli (2018), the evolution in time of the shock in the final stages of the evolution may be affected rather remarkably by the CR pressure, and the beginning of the radiative phase may be delayed. We do not include these effects here.…”
Section: Evolution Of the Shock In The Circumstellar Environmentmentioning
confidence: 99%
“…For example magnetic fields, cosmic rays (e.g. Diesing & Caprioli 2018;Gupta et al 2018) and thermal conduction (e.g. Keller et al 2014;El-Badry et al 2019) change their evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Remnant Evolution-SNRs are evolved using the formalism described in [20]. More specifically, SNR evolution can be understood in terms of four stages: the ejecta-dominated stage, in which the mass of the sweptup ambient medium is less than that of the SN ejecta, the Sedov stage, in which the swept-up mass dominates the total mass and the SNR expands adiabatically, the pressure-driven snowplow, in which the remnant cools due to forbidden atomic transitions but continues to expand because its internal pressure exceeds the ambient arXiv:1905.07414v2 [astro-ph.HE] 26 Jul 2019 pressure, and, finally, the momentum-driven snowplow, in which the internal pressure falls below the ambient pressure and expansion continues due to momentum conservation.…”
mentioning
confidence: 99%